2007
DOI: 10.1002/term.51
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose as a potential meniscus implant

Abstract: Traumatic or degenerative meniscal lesions are a frequent problem. The meniscus cannot regenerate after resection. These lesions often progress and lead to osteoarthritis. Collagen meniscal implants have been used in clinical practice to regenerate meniscal tissue after partial meniscectomy. The mechanical properties of bacterial cellulose (BC) gel were compared with a collagen material and the pig meniscus. BC was grown statically in corn steep liquid medium, as described elsewhere. Pig meniscus was harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(90 citation statements)
references
References 6 publications
2
88
0
Order By: Relevance
“…This may be due to microbial contamination of the porcine urinary bladders that led to the presence of endotoxins in the UBM solution. Similar endotoxin results have been reported for BC scaffolds produced by G. xylinus ATCC ® 700198™ for tissueengineered urinary conduits [39].…”
Section: Substrate Characterizationsupporting
confidence: 86%
See 2 more Smart Citations
“…This may be due to microbial contamination of the porcine urinary bladders that led to the presence of endotoxins in the UBM solution. Similar endotoxin results have been reported for BC scaffolds produced by G. xylinus ATCC ® 700198™ for tissueengineered urinary conduits [39].…”
Section: Substrate Characterizationsupporting
confidence: 86%
“…C), both samples showed similar stress-strain behavior, with stress increasing with strain increment until the sample collapse. The presence of UBM resulted in a 3-fold increase in the elastic modulus ( ), which suggests that it strongly adheres to sample fibers [19,39]. A porous surface could be observed in Fig.…”
Section: Substrate Characterizationmentioning
confidence: 84%
See 1 more Smart Citation
“…Due to its good tensile mechanical properties, BNC has been used in previous work for blood vessel (Bodin et al, 2007a;Klemm et al, 2001;Malm et al, 2012), meniscus (Bodin et al, 2007b;Martinez et al, 2012), and articular cartilage tissue engineering (TE) strategies (Andersson et al, 2010;Svensson et al, 2005). It has been shown that BNC supports adhesion and proliferation of different cell types (Andersson et al, 2010;Backdahl et al, 2006;Bodin et al, 2010;Brackmann et al, 2011;Svensson et al, 2005), in particular chondrocytes (Andersson et al, 2010;Svensson et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Natural materials used to date are: periosteal tissue (Walsh et al, 1999); perichondral tissue (Bruns et al, 1998); small intestine submucosa (SIS) (Cook et al, 1999); acellular porcine meniscal tissue (Stapleton et al, 2008); and bacterial cellulose (Bodin et al, 2007). While these tissues have high biocompatibility, some of them cannot be employed for tissue engineering techniques as they do not allow varying structure geometry and initial mechanical properties .…”
Section: Scaffoldsmentioning
confidence: 99%